The Effect of a Fermented Soy-Based Dietary Food Product on Blood Lipids in Individuals at High Risk for Cardiovascular Disease - Jung, Sarah; Sirirat, Rawiwan; Kim, Alice; Amen, Rita; Kaur, Amandeep; Ianchis, Alissa; Oda, Keiji; Haddad, Ella; Sabaté, Joan (Current developments in nutrition, 2020)
Previous reports indicate that intake of some soy products may be associated with improvements in blood lipids but few studies examined fermented soy foods. Q CAN PLUS® is a functional food product derived from fermented soybeans. To evaluate the effects of fermented soy on cardiovascular risk factors, we implemented a clinical trial to compare the effects of the fermented soy powder (Q CAN PLUS®) against a placebo (sprouted brown rice powder) in individuals at risk for cardiovascular diseases. Twenty-seven adults at risk for cardiovascular diseases (29–75 years old; 78% female; mean BMI [32.3 kg/m2 ± 7.3]) were randomized to consume either 2 pouches (12–15 g powder/pouch) per day of fermented soy powder (Q CAN PLUS®), or a sprouted brown rice powder for 12 weeks each, in a crossover design trial. The intervention phases were separated by a two week wash out period. Measurements and biospecimens were taken at baseline and at weeks 11 and 12 of each phase. Assessment included blood lipids, blood pressure, blood glucose, blood insulin, and anthropometric measures. For each of the outcomes, a mixed model was fitted to compare changes from pre- to post-treatment and between treatments. The models included treatment, time, interaction between treatment and time, phase, visit within phase and enrollment period as fixed effects terms and subjects as random effects terms. Between treatment results from the mixed model analysis show that fermented soy powder intake significantly reduced serum cholesterol (mean change –8.95 mg/dL; P = 0.0024), LDL (mean change –6.96 mg/dL; P = 0.0317), and HDL (–1.29 mg/dL; P = 0.0036) compared with the sprouted brown rice powder. Within treatment results indicated that fermented soy powder significantly reduced total cholesterol (P = 0.0073) and LDL (P = 0.0132), while reductions in HDL were not statistically significant. Within treatment results were not statistically different for the placebo phase except for an increase in HDL (mean change 3.61; P = 0.0026). These data indicate that regular intake of fermented soy powder results in a reduction in serum total and LDL cholesterol which may have beneficial implications for the reduction of cardiovascular risk factors in adults. BESO Biological Research Inc. Diamond Bar, CA, USA.